STRUKTUR MODAL : PENGUJIAN PECKING ORDER THEORY PADA SIKLUS HDUP PERUSAHAAN GROWTH DAN MATURE - Darma, Putri Ekawati (Jurnal MS, 2014)
This study examine whether growth and mature firms in the manufacturing sectorÂ of Indonesia follow the packing order theory. Futhermore, the company researched whether the stongergrowth tends to follow the packing order theory than mature. The sample were companies in the manufacturing industry 2007 â€“ 2011. Hypothesis testing using multiple regresion analysis and augmented model.Â Based on classification, companies growth tends to more than mature. The resultÂ analysis showcompany growth experienced deficiency cash grather than the mature.Â Analysis of the results also indicated that group of the company which followÂ packing order theory is a company growth. It is shown from a correlation betweenÂ Â deficiency cash with additional debt new issue. These results indicated by aÂ coefficient deficit squared is negative and deficit is positive. While based onÂ analysis to the company mature exhibit no packing order theory because theÂ result of testing no significant. Based on the findings, it is concluded that group ofÂ the company economic growth experienced a shortage of cash greater than that ofÂ mature. The group of companies that follow the packing order theory is theÂ company growth. Group of the company growth also tends more strong follow pecking order theory than mature.Â